The Mechanism of Fibrinolysis Induced by Bacterial Pyrogens - Deutsch, E; Elsner, P; with the technical assistance of; Marschner, I (Thrombosis and Haemostasis, 1959)
1. The mechanism of the activation of plasmin in blood after intravenous injection of bacterial pyrogens was studied.2. There was plasmin and an activator present in the spontaneous lytic blood samples. In cases with a high level of plasmin a low amount of plasminogen was found and vice versa.3. There seem to be two mechanisms of activation. In the most cases the activator has the properties of a fibrinokinase. In the other type a fibrinolysokinase was found.4. The resistence of the activator against changes in pH and influence of temperature was studied. It was found that the activator was very resistent at acid pH, and, therefore, it shoud be classified as a stable type activator. In addition to this a small amount of a labile type activator seems to be present.5. Some fibrinolytic activity develops in vitro if the pyrogens are incubated with cell-containing plasma or blood. It is supposed that the leucocytes are involved in the activation mechanism.